Returning of Asian Glory - Ahmed, Ali; Panda, Jagannath P.; Singh, Prashant K.; Aneet (Gyan Management Journal, 2012)
’Towards a New Asian Order’ is one of the first attempts to identify and present in an organized manner the issues that beset the continent. Asia faces a lot of hurdles. The continent is plagued by terrorism and instability, which is further complicated by natural calamities and issues of energy, water and overpopulation. This book is a collection of papers written by eminent scholars and experts on the various aspects and facets encompassing Asia, edited by Dr Ali Ahmed, Dr Jagannath P. Panda and Dr Prashant K. Singh, all three associated with the Institute for Defence Studies and Analysis, New Delhi.It has become imperative to find the tools for mutual growth for the collective development of Asia. The twentieth century saw two world wars and India for one has had to deal with three full-fledged wars and some major conflicts like the one in Kargil. The weaponry used has become increasingly sophisticated and with the growing arsenal with each country, some form of mutual understanding has become the need of the hour. The book aims to ’survey existing capacities against possibilities’, rightly pointing out that the future trajectory of Asia is going to depend on how the Asian societies resolve their respective socio-political dilemmas.